Antibacterial Activity and Qualitative Phytochemical Analysis of Selected Seaweeds from Gulf of Mannar Region - Sekaran Sridhar1*, Jebamalai Suresh Kumar1 and Sarangam Babu2, Periasamy Mansuya1, Pandurangan Aruna1 (Journal of Experimental Sciences, 2010)
<div style="border-bottom: medium none; border-left: medium none; padding-bottom: 0in; padding-left: 0in; padding-right: 0in; background: white; border-top: windowtext 1pt solid; border-right: medium none; padding-top: 1pt; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> The phytochemical analysis of the aqueous extracts of some commonly occurring green seaweed Cladophora glomerata, Ulva lactuca and Ulva reticulata, the red seaweed Gracilaria corticata and Kappaphycus alvarezii and the brown seaweed Sargassum wightii and their evaluated for antibacterial activity by well diffusion assay. Two different solvents namely aqueous and methanol were used for extraction. The phytochemical analysis revealed the presence of Carbohydrates, Alkaloids, Steroids, Tannin & Phenols, Saponins, Fixed oils & Fats, Gums & Mucillage, Proteins, Flavonoids and Volatile oils in varying concentration. The zone of inhibition ranged between 45 – 9mm in aqueous extract and 40 – 6mm in methanolic extract. The maximum activity (45mm) was recorded from 200mg of aqueous extract of Ulva reticulata against Salmonella typhi and minimum (9mm) by Ulva lactuca against Streptococcus pyogenes at 50mg level whereas, the methanolic extract showed the maximum activity (40mm) was recorded from 200mg of U. reticulata against Escherichia coli and Streptococcus pyogenes and Cladophora glomerata against Pseudomonas aeruginosa and minimum (6mm) by 50mg of Kappaphycus alvarezii against Staphylococcus epidermis. --- 1Department of Botany, Govt. Arts College, Thiruvannamalai – 606 603, Tamil Nadu, India; 2Aquagri Processing Pvt. Ltd., Manamadurai, Tamil Nadu, India --- Please Cite This Article As: Periasamy Mansuya, Pandurangan Aruna, Sekaran Sridhar, Jebamalai Suresh Kumar and Sarangam Babu. 2010. Antibacterial Activity and Qualitative Phytochemical Analysis of Selected Seaweeds from Gulf of Mannar Region. 1(8):23-26.